Extracellular Vesicles, as Drug-Delivery Vehicles, Improve the Biological Activities of Astaxanthin - Young Jun Jang; Byung Seok Cha; Doyeon Kim; Eun Sung Lee; Seokjoon Kim; Jinjoo Han; Jiye Shin; Seokhwan Kim; Ki Soo Park (MDPI AG, 2023)
Astaxanthin (AST) exhibits potent antioxidant and anti-inflammatory activities but poor stability and biological efficacy, which limit its application in the food and medical industries. In the present study, a new strategy was proposed to enhance the biological activities of AST using fetal bovine serum-derived extracellular vesicles (EVs). Saponin-assisted incubation was used to load AST owing to its high encapsulation efficiency and loading capacity. AST-incorporated EVs (EV-ASTs) maintained their original EV morphology and showed high stability at 4 °C, 25 °C, and 37 °C over a 28-day period, which was attributed to the protective environment provided by the phospholipid bilayer membrane of the EVs. Additionally, the EV-ASTs exhibited excellent antioxidant and anti-inflammatory activities in HaCaT keratinocytes and RAW 264.7 macrophage cells, respectively; these were significantly higher than those of free AST. Furthermore, the mechanism associated with the enhanced biological activities of EV-ASTs was evaluated by analyzing the expression of genes involved in antioxidation and anti-inflammation, in parallel with cellular in vitro assays. These results provide insights into methods for improving the performance of hydrophobic drugs using nature-derived EVs and will contribute to the development of novel drug-delivery systems.